Licenciamento ambiental, repensando a ferramenta : estudo de caso em tipologias não industriais nos ecossistemas costeiros da Região dos Lagos no Rio de Janeiro - Pereira, Luiz Firmino Martins (2009)
The ecosystems of coastal areas has been affected by the uncontroled ocupation of land, basicaly because, although fragile environments, its attractiveness has raised immobiliary projects. In this studies it is carried out an evaluation of the management instrument of enviromental licence at Rio de Janeiro State (SLAP), focusing on non industrial activities of the Região dos Lagos (Lagoons Region, East of Rio de Janeiro city), identifying its problems. During the study, it was made an analysis of the enviromental license processes between 1999 and 2002, that were classified in the subjects, time of answer, location and possible impacts. The study indicated that the raised data obteined from the license process presently operated in the State of Rio de Janeiro is failling to protect the environment and a new system has to be urgently developed. Concluded in propose a new kind of model, which bring about the professionals and companies that work within this area like a co-responsable personality together whit the State Enviromental Agency. The study also proposes more social control mechanisms and a reduction of the financial control of the enterprises that contract Enviromental Impact Studies.